Five new phorbol esters with cytotoxic and selective anti-inflammatory activities from Croton tiglium. Issue 9 (1st May 2015) - Wang, Jun-Feng; Yang, Sheng-Hui; Liu, Yan-Qun; Li, Din-Xiang; He, Wei-Jun; Zhang, Xiao-Xiao; Liu, Yong-Hong; Zhou, Xiao-Jiang
Graphical abstract